2004
DOI: 10.1021/bi049053+
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Phenylalanine Ammonia Lyase:  Multiple Helix Dipoles Implicated in Catalysis,

Abstract: The first three-dimensional structure of phenylalanine ammonia lyase (PAL) has been determined at 2.1 A resolution for PAL from Rhodosporidium toruloides. The enzyme is structurally similar to the mechanistically related histidine ammonia lyase (HAL), with PAL having an additional approximately 160 residues extending from the common fold. We propose that catalysis (including lowering the pK(a) of nonacidic C3 of l-phenylalanine for an E1cb mechanism) is potentially governed by dipole moments of seven alpha hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
161
0
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(178 citation statements)
references
References 52 publications
8
161
0
9
Order By: Relevance
“…A conserved Ala-Ser-Gly segment which is typical for ammonia-lyases can also be found in sam8 (4,24). Furthermore, several active-site amino acid residues proposed for HAL after elucidation of the X-ray structure of HutH, a HAL from Pseudomonas putida, have analogous residues in Sam8 (22,24).…”
Section: Resultsmentioning
confidence: 94%
“…A conserved Ala-Ser-Gly segment which is typical for ammonia-lyases can also be found in sam8 (4,24). Furthermore, several active-site amino acid residues proposed for HAL after elucidation of the X-ray structure of HutH, a HAL from Pseudomonas putida, have analogous residues in Sam8 (22,24).…”
Section: Resultsmentioning
confidence: 94%
“…It is also the only general phenylpropanoid pathway enzyme for which detailed structure-function information is available. The first structures of bacterial and plant PALs were solved in 2004 [10,55]. Other bacterial and fungal PAL/TAL structures were elucidated more recently [45,47].…”
Section: Branching Out From Primary Metabolism: the General Phenylpromentioning
confidence: 99%
“…In TAL, the first of these segments is packed tightly within the active-site cleft and interacts closely with the bound substrate/product molecule, whereas the second segment forms a more external loop that caps the active-site region. These loops appear to be intrinsically flexible in the PAL proteins, as they are also poorly ordered in the structures of parsley and yeast PAL (9,10). In the crystal structures of the cyanobacterial PALs, the active-site cleft appears very exposed to the external solvent, and the absence of stabilizing interactions contributed by the disordered inner loop is a likely reason for the failure to observe stable binding to these PALs of the substrate (L-Phe), the product (cinnamic acid), and a potent PAL-specific inhibitor (2-aminoindan-2-phosphonic acid) (31).…”
Section: Mio and Modeling Of Substrate In The Active Sitementioning
confidence: 99%
“…In total, these structure determinations showed that the ammonia-lyases exist as homotetramers possessing a conserved polypeptide-chain fold. The eukaryotic PALs are ~20 kDa per monomer larger than the prokaryotic HALs, by virtue of a 54-residue N-terminal extension and an inserted 122-residue domain (9)(10)(11). The additional domain in the plant and fungal enzymes forms an arch over the active site and has been proposed to function as a shielding domain by restricting substrate entry and product egress (10).…”
mentioning
confidence: 99%